Prognostic significance of intrathecal oligoclonal immunoglobulin G in multiple sclerosis - Grgic, Sanja; Dominovic Kovacevic, Aleksandra; Djajic, Vlado; Vukojevic, Zoran; Tadic, Daliborka; Racic, Dusko; Vujkovic, Zoran (Scripta Medica, 2020)
Introduction/Aim: Detection of intrathecal oligoclonal bands of immunoglobulin G (OB IgG), in addition to diagnostic, has a predictive significance in multiple sclerosis (MS). The aim of the study was to determine the prognostic significance of OB IgG and to correlate the presence of OB IgG with the progression of disability in MS patients. Methods: A retrospective-prospective cohort study included 177 MS patients examined at the Centre for MS, Clinic of Neurology, University Clinical Centre of the Republic of Srpska. In all patients, demographic data, clinical parameters, Expanded Disability Status Scale (EDSS) score, isoelectric focusing (IEF) of cerebrospinal fluid (CSF), cyto-biochemical analysis of CSF, evoked potentials (EP) and magnetic resonance (MR) of the head were analysed. MS patients were divided in two groups: with and without intrathecal synthesis of oligoclonal IgG. According to the EDSS determined in both groups, the relation between the degree of functional disability and the presence of OB in the CSF and also with characteristics of the cyto-biochemical profile were analysed. Methods of descriptive and analytical statistics, analysis of variance, chi-square test, Bonferroni’s post hoc test, correlation and regression analysis were used in the analysis of the results. Results: In the examined cohort of MS patients, the sensitivity of IEF was 96.6 %. There was a statistically significant association between the detectability of intrathecally synthesised IgG and EDSS score (p = 0.004) so that individuals who do not have intrathecally synthesised IgG had lower EDSS scores. MS patients with a CSF protein concentration > 0.40 g/L were 2.45 times more likely to enter secondary progression and 2.51 times more likely to achieve EDSS 4.0. Conclusion: IEF is a very sensitive diagnostic and prognostic method for MS patients, which indicates a more benign course of MS in patients without oligoclonal bands in the CSF.